Achieving compliance with pool fencing legislation in New Zealand: a survey of regulatory authorities. Issue 2 (1st June 1999) - Morrison, Luke; Chalmers, David J; Langley, John D; Alsop, Jonathan C; McBean, Catriona
Abstract : Objectives —To identify the status of compliance and enforcement of New Zealand's Fencing of Swimming Pools Act (FOSP Act), 10 years after its introduction, and to identify methods for improving both compliance with the act and the process of enforcement. Methods —A postal questionnaire was sent to all 74 authorities in New Zealand in which they were asked questions about their enforcement of the FOSP Act. Semistructured telephone interviews were conducted with 12 authorities to supplement the data obtained in the postal survey. Results —Based on responses to the survey, it was estimated that there are over 59 000 domestic swimming pools in New Zealand, giving rates of 46 pools/1000 dwellings and 16 pools/1000 persons. The authorities reported that 44% of pools complied with the act, and a further 4% had been granted exemptions. Nineteen per cent of pools were reported to not comply with the act, and the compliance status of a further 33% was not known, or not stated by the authority. Only 9% of authorities had procedures for locating and inspecting pools, while 28% had a programme of reinspection to ensure that pools continued to comply. Pool owner resistance was considered to be the main difficulty with enforcing the act, and nearly half of the authorities believed publicity or education was needed to overcome these barriers. Fifty two per cent of authorities had publicised the act during the 12 months preceding the survey. Conclusions —Due to ambiguities within the legislation, and differing levels of commitment by authorities to locate pools and monitor compliance, compliance with the FOSP Act is not consistent nationally. If the act were less ambiguous, there would be greater consistency and more enforcement.